Optimizing the thermal gradient and the pulling speed in a thermoplastic pultrusion process of PET/E glass fibers using finite element method - Nataša Z Tomić (Metallurgical & Materials Engineering, 2018)
A thermoplastic pultrusion process was examined using commercial fiber roving of PET/E glass, to determine the optimum pulling speed and optimal zonal temperatures. Finite element analysis predicted heat transfer through the commingled fibers and air in the pultrusion die. The cross-section of obtained rods was examined, and image analysis was carried out to obtain information about the degree of fiber impregnation, number of voids and uniformity of fiber distribution. Optimizing the temperature field for the pultrusion of poly (ethylene terephthalate) is of significant importance. The pulling speed has the same importance. These two parameters are closely related as evidenced by the analysis of images.